The Role of Toys in the Development and Upbringing of a Child in the Process of Education and Upbringing - Tashtemirova Fazilat Eshmuratovna (Zien Journals, 2022)
Game is a process of movement and understanding of objective and social reality. It is a social reality in its origin, direction and content. Play is a brilliant form of children's activity. The presence of a goal, reasons, planned actions, means of implementation, the presence of a result are its features. Among the features, the main one is the specificity of the causes. During the game, the child develops a mental cognitive process, will, feelings, needs and interests, emotions - the whole personality. The basis of the game, of course, are toys. A toy is a toy that a child can play with and not use for other purposes. It reflects the typical features of the child as a whole.
Keywords: game; toy; require; cubes